MODERNIZATION OF THE CLASSIC REPRESENTATION OF MORAL OBLIGATION IN VIRTUE ETHICS BY A. MACINTYRE - L. R. Askhanova (Дискурс, 2017)
This article considers the main ideas of the leading representative of American political philosophy and ethics Alasdair MacIntyre regarding morality and obligation set out in his fundamental work "After virtue". In the never-ending discussion of moral problems and chaos in the value-normative sphere, MacIntyre suggests reconsidering the Aristotelean tradition of virtue with its teleological basis for morality and its central concepts of good, virtue, duty and purpose. Not being a supporter of abstract moral theorizing, MacIntyre insists on the primary connection between morality and practical rationality through moral arguments centered on the experience of social practices of the community in the search of the common good.